Application of diluted methanol to allow the production of latex modified asphalt mixture with lower energy consumption. (30th November 2020) - Aziz, Muhammad Khuzaimi; Mohd Hasan, Mohd Rosli; Poovaneshvaran, Sharvin; Tai, Guo; Wang, Hainian
Highlights: This paper evaluates usage of diluted methanol as a foaming agent (FA) in latex WMA. Diluted methanol expand the latex modified binder's volume and lower its viscosity. Hence, allows the production of latex modified asphalt mixture at lower temperature. Application of methanol improve the service characteristics and mixture performance. Incorporation of diluted methanol could promote environment sustainability. Abstract: The modification of asphalt mixtures using latex has gained popularity in the asphalt industry as it improves the durability of road pavement. However, the elastomeric properties of latex stiffen the binder, resulting in more energy consumption during the asphalt mixture production. It would consequently cause a higher emission of greenhouse gases, which is undesirable for the human health and environment. This study aims to assess the applicability of diluted methanol as a foaming agent in asphalt mixture incorporating latex produced at a lower temperature. In this study, two designated amounts of diluted methanol (1% and 3% of the weight of asphalt binder) were successively injected with 6% latex into pre-heated asphalt binder at 135 °C in the preparation of foamed binders, while the control and latex modified asphalt mixtures were prepared at 160 °C. Tests of rotational viscosity, expansion rate, and torsional recovery were conducted to study the rheological properties of the mixtures. Service characteristics were evaluated through the indices of workability, compaction energy, and coatability. Moreover, mixture performance tests were carried out to identify the tolerance of the mixtures towards moisture damage, shear force, and permanent deformation. Through the rotational viscosity test, diluted methanol was found to reduce the viscosity of the asphalt binders, which is vital in the production processes at intermediate temperatures. The enhancement in viscosity using 3% diluted methanol had facilitated in higher workability, lower compaction energy, and better aggregate coating, which are the crucial criteria for a better mixing and compaction process. Whereby, a superior foaming quality was exhibited from the 3% diluted methanol application through the assessments of expansion ratio, half-life and foaming index. The moisture and shear resistances of the diluted methanol foamed asphalt mixtures are comparable to the control mixtures even though they were prepared at a lower temperature. Finally, the 3% diluted methanol foamed asphalt mixture promoted a better rutting resistance due to its ability to recover to the initial form which was demonstrated through its torsional recovery.